PLEASE ANSWER

Asked by  | 4th May, 2009, 04:50: PM

Expert Answer:

X = 3+32/3+31/3

This series is a GP 31/3 + 32/3 + 33/3

First Term = 31/3

Common ratio = 31/3

Sum = X = 31/3 + 32/3 + 33/3

                 = 31/3 ((31/3)3 - 1)/ (31/3 - 1))

                 = 31/3 (2)/ (31/3 - 1)

                 = 2 . 31/3/ (31/3 - 1)

Substituting the value of 31/3 , we get the value of X = 6.5

Now to compute the value of expression X3 -9X 2 +18X -12 substitute X = 6.5

X3 -9X 2 +18X -12 = (6.5)3 -9(6.5) 2 +18(6.5) -12

                                 = -0.625

 

 

Answered by  | 1st Sep, 2009, 04:15: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.